Comparative assessment of faecal sludge management (FSM) system's environmental and health impacts on neighbouring communities in Dhaka, Bangladesh - Hossain, Alamgir; Thammarat Koottatep; Ghimire, Anish; Chongrak Polprasert; Global Water & Sanitation Center (GWSC); AIT Scholarship (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
Achieving Sustainable Development Goal 6.2 requires strengthening faecal sludge management (FSM) through Citywide Inclusive Sanitation (CWIS) approaches that promote equitable, safe, and sustainable urban sanitation. In Dhaka, both informal and formal settlements rely predominantly on on-site sanitation systems that frequently discharge untreated waste into drains and water bodies, posing severe environmental and public health risks. This study compared FSM performance in two contrasting neighbourhoods, Korail and Gulshan, to examine how failures across the sanitation service chain influence lake pollution and human exposure.A quantitative explanatory sequential mixed-methods design was employed using three diagnostic tools: the Shit Flow Diagram (SFD) to quantify excreta flows; the City Service Delivery Assessment (CSDA) to evaluate governance and institutional performance; and the SaniPath Exposure Assessment to estimate human exposure to faecal contamination across multiple environmental and behavioural pathways. Water-quality analyses quantified pollutant loads entering Banani Lake. All findings were integrated into the CWIS framework to assess performance across its six pillars.Results revealed extremely low levels of safely managed sanitation, 2% in Korail and 3% in Gulshan, reflecting systemic failures across both sewered and non-sewered systems. In Korail, widespread lack of containment led to direct discharge into drains, absence of investment planning, and weak oversight. In Gulshan, non-functional sewers, limited funding, and unregulated desludging resulted in untreated wastewater entering the drainage network. Weak coordination, inadequate monitoring, and limited regulatory enforcement were evident in both areas. Pollution-load analysis showed that Korail contributed nearly five times more faecal contamination to Banani Lake than Gulshan. SaniPath results indicated high exposure in Korail through drains, drinking water, street food, and raw produce, while food-borne pathways dominated exposure in Gulshan. Collectively, the findings highlight major gaps across all CWIS pillars and reveal Dhaka{u2019}s 2sanitation paradox3: an absence of service in low-income settlements and an illusion of service in affluent neighbourhoods.The study concludes that improving containment standards, establishing a dedicated FSM Cell, rehabilitating sewer networks, strengthening regulatory enforcement, securing dedicated sanitation budgets, promoting behaviour-change interventions, and expanding inclusive sanitation services are essential to reducing environmental contamination, protecting public health, and accelerating progress toward safely managed sanitation under SDG 6.2.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Environmental Engineering and Management
Thesis (M. Eng.) - Asian Institute of Technology, 2025
Keywords: Urban sanitation -- Bangladesh -- Dhaka -- Management; Sustainable development -- Bangladesh -- Dhaka